Selection of mode of tandem dragline operations by utilizing 3-dimensional computer graphics balancing diagram: A case study - Seervi V.; Kishore N.; Verma A.K. (My University, 2025)
With the expansion of mines for higher rated outputs, the operation of a dragline in tandem has gained significance in the field. The tandem operation enhances capacity utilization of draglines which are highly capital-intensive equipment. To maximize the return on investment and improve the dragline’s performance, its mode of operation and influencing parameters must be understood and carefully analysed. The balancing diagram (a graphical representation of dragline cuts and spoil geometry) for the draglines operating in tandem is the most essential tool to deploy the dragline successfully. This task manually is normally both difficult and time-consuming and requires an analytical solution. This is best suited to the  application of computer graphics methods. Therefore, a balancing diagram in a 3-dimensional graphics package has been developed to assist the mine planner in planning dragline operations. The purpose of this paper is to select the most appropriate mode of dragline operation, operating in tandem, and by analysing the two indices, i.e., rate of coal exposure and percentage rehandle. The analysis will be case studyoriented with practical mining considerations and comparatives indices being formulated for better understanding. In the present study, field data pertaining to the dragline operations have been collected from one of the prestigious mines of Northern Coalfields Limited, a subsidiary of Coal India Limited, and an attempt has been made to decide the mode of operation under the existing field conditions. © 2022, Books and Journals Private Ltd.. All rights reserved.